Análise comparativa dos fatores comuns encontrados na implantação do Total Productive Maintenance (TPM) - Quintino, Camila de Fátima Goilevicz (2017)
Currently, companies need to seek strategies to increase productivity, to improve quality and to reduce costs. Thus, to meet customers’ needs and requirements. One of the philosophies used to achieve these improvements is Total Productive Maintenance (TPM). This methodology helps to reduce the occurrence of equipment failure. Its goals are: zero breakdown, zero accidents, zero defects and the increase of efficiency of the administrative processes and equipment. This paper`s aim is a comparative analysis of Total Productive Maintenance implementation in different industries, analyzing the barriers and success factors found in TPM implementation and the impact of the country and organization culture on the success of the TPM. It can be verified that full employee involvement is a prerequisite for a successful implementation of TPM.